ADDENDUM to Roca-Cusachs, M. & Goula, M. 2016. New genus and species of ant-like true bug (Hemiptera: Miridae) from the Canary Islands. Zootaxa 4173 (1): 066–074. - Roca-Cusachs, Marcos; Goula, Marta (Zootaxa, 2016)
Genus Perenotus and species Perenotus malobae were recently described as a new genus and species by Roca-Cusachs & Goula (2016). Article 16.4.2 of ICZN (1999) requires a statement of intent that the holotype is deposited in a collection and a statement indicating the name and location of that collection. Unfortunately, it is unclear if this requirement was satisfied.